Minimal Invasive Rhinoplasty: Fat Injection for Nasal Dorsum Contouring. (March 2017) - Lin, Susie; Hsiao, Yen-Chang; Huang, Jung-Ju; Chang, Chun-Shin; Chen, Philip Kuo-Ting; Chen, Jyh-Ping; Lo, Lun-Jou; Chen, Yu-Ray
Abstract : Purpose: To determine the graft retention rate of fat injection rhinoplasty in the nasal dorsum region using 3dMD System. Materials and Methods: Thirteen consecutive patients (12 women and 1 man) treated by the corresponding author (F.C.S.C.) between April of 2014 and December of 2015 for autologous fat injection rhinoplasty at the nasal dorsum region to improve facial esthetics were included in this study. Preoperative and postoperative 3-dimensional (3-D) photography images taken 3 months after fat injection rhinoplasty were superimposed at the level of forehead to measure the volume changes at the nasal dorsum region. The same evaluator repeated the measurements 1 week after the initial measurements. Pearson correlation test was used to determine the intraobserver correlation. Results: Twenty-six scans from 13 patients were analyzed. The amount of fat injected for nasal dorsum augmentation was 1.67 ± 0.95 mL (range, 0.6–3.3 mL). The volume changes calculated using the 3dMD system was 0.74 ± 0.42 mL for the first measurements and 0.74 ± 0.43 mL for the second measurements. The Intraobserver consistency was high with Cronbach α = 0.96 ( P < 0.001). The mean volume change according to 3-D photography was 0.74 ± 0.42 mL (range, 0.21–1.53 mL). The mean retention rate was 44.54% (range, 21–74%). Conclusions: In this pilot study, we reported the fat graft retention rate for nasal dorsum augmentation using 3-D photography. Future studies with a larger sample size, longer-term follow-up, and different anatomical regions will be beneficial to better understand the long-term fat graft retention rate.